Exploring the Role of Entrepreneurial Skills Competence and Networks in Enhancing MSME Performance Evidence from a Developing Economy - Nandez, Mechila; Esayne, Eneolla (Inovasi Analisis Data, 2024)
Purpose: The objective of this study is to investigate the nexus of relationship among entrepreneurial skills as well as market orientation and sales orientation with business networks and performance of micro, small and medium enterprises (MSMEs) of a developing economy.Method: We conducted a strong quantitative research design by using structured questionnaires based on established scales to measure the core variable. MSMEs across various sectors in Nigeria were recruited through a purposive sampling method, and the data were analyzed through multiple regression and mediation method, based on the directions of Baron and Kenny 1986.Findings: The results show that entrepreneurial competence, market orientation, sales orientation and business networks had direct and indirect relationships with firm performance. The essential in these entrepreneurial characteristics on the overall performance of MSMEs was mediated by entrepreneurial competence as an important factor. Conclusions: These findings underscore the multidimensional nature of MSME performance and present entrepreneurial competencies as important drivers of firm growth and continuity.Novelty: This study is amongst the first to analyse the mediating role of entrepreneurial competence within the MSME context of a developing country, Nigeria. The research extends knowledge on emerging market entrepreneurial dynamics by integrating multiple environmental perspectives with advanced mediation analysis technique, explaining how why diverse entrepreneurial phenomena work in concert to reward entrepreneurs in emerging markets through business outcomes.Implications: he study highlights implications for managers of MSMEs, policymakers, and researchers, underlining the significant role of entrepreneurial competency improvement in enhancing business performance. It shows that having a skills, market orientation, and strong business network can help the MSMEs that may benefit them grow stiffened in a competitive market.